ASEAN Centered Regional Architecture in Managing Sustainable Investment Under the RCEP - Koesrianti (Faculty of Law, Universitas Brawijaya, 2024)
Regional Comprehensive Economic Partnership (RCEP) that consist of 15 Asian member countries established in 2021 which to achieve a trade liberalization in the region. The Asian countries have been recognized as the motor of global regionalism and have heightened the Asian region become the center of global economy. This article aims to examine the provisions of RCEP on trade in investment whether it supports sustainability of investment in the region. The region will become a seamlessly market as the region is a market with free flow of goods, services, and investment. While the result of the Pact has not identified yet, this agreement constitutes as a significant effort of ASEAN as one entity, taking the lead of the implementation RCEP, in this current legal regime to gain leverage over its dialogue trade partners. In light of this, the current article’s objective is to observe and evaluate the overall role of ten ASEAN Member States (AMS) which work together to collectively in advancing their part in RCEP by comparing RCEP with International Partnership Economic Framework (IPEF). This study is multidisciplinary research using collected research materials include data and information that have been analyzed from legal and economic perspectives using qualitative descriptive method and found that RCEP investment provisions are utilized to support, realize and attain the ASEAN’ grand strategy to achieve and maintains sustainability of investment in this new Asian regionalism.